Dimenzioniranje in izvedba sodobne dvostopenjske hladilne naprave - Dimnik, Marjan (Strojniški vestnik, 2000)
In the paper the methodology for the dimensioning and construction of two-stage cooling device, which could operate as a single-stage also, is presented. Emphasis is laid on the calculation of the component parts in comparison with standard single-stage device. Furthermore a construction process, testing and measurements on experimental device, which successfully operates with single- or two stages, are described. At the end it is proofed that in case of higher differencis between evaporation and condensation pressure it is reasonable to deside on two-stage cooling device.
Keywords: procesi hladilni; moč hladilna; moč grelna; naprave hladilne; hladilne naprave; dimenzioniranje; hlajenje